Heart size, heart function, and plasma B-type natriuretic peptide levels after transcatheter closure of patent ductus arteriosus - Mulyadi M. Djer; Sudigdo Sastroasmoro; Bambang Madiyono (Indonesian Pediatric Society, 2013)
Background Patent ductus arteriosus (PDA) is a commoncongenital heart disease causing some blood in the aorta to flowinto the pulmonary artery (PA), resulting in dilatation of the leftatrium (IA) and left ventricle (LY), increased B-type natriureticpeptide (BNP) level, and the development of h eart failure.Objectives To evaluate the clinical course, changes in heart sizeand function, and BNP level after transcatheter closure of PDAusing the AmplatzerÂ® duct occluder (ADO).Methods This quasi-experimental study used a one-group, pretestposttestdesign, and was done on PDA patients who underwenttranscatheter closure using ADO. The outcomes measurementswere performed four times, namely, before the procedure andat one, three, and six months after the procedure. Results werecompared using a serial time analysis. Outcomes measured wereheart failure scores, chest x-ray (CXR) and echocardiographyfindings, and plasma BNP level.Results There were 23 PDA patients enrolled, of which 12 werefemales. Subjects' median bodyweight was 11 (range 6.6 to 55) kg.Prior to PDA closure, 12 subjects had mild heart fa ilure (class II)and 7 had moderate heart failure (class III). On follow-up at onemonth after the procedure, all subjects had improved heart failurescores (P<0.0001), and no heart failure was found on furtherfollow up. Likewise, there was a decreased mean cardiothoracicratio (CTR) from 58 to 55% at 1-month (P = 0.001), and alsofrom 55 to 52% at3-month follow up (P<0.0001), but no furtherdecrease was found afterwards (P = 0.798). The left atrium/aorta(LA/Ao) ratio measured by echocardiography also showed astatistically significant decrease from 1.6 prior to the procedureto 1.3 (P<0.0001) in the first month, but it remained stableafterwards. Diastolic function, represented by peak E and A wavesalso significantly decreased from 127 and 91 cm/sec, before theprocedure, to 90 and 68 cm/sec, respectively, at 1 month follow-up(P <0.0001 and P < 0.0001, respectively) . However, there were nostatistically significant changes in E/ A ratio, ejection fract ion andfractional shortening. Plasma BNP level significantly decreasedfrom 58 pg/mL before the procedure to 28 pg/mL at 1 monthfollow-up (P= 0 .001), but no further significant decrease wasobserved afterwards.Conclusion After PDA closure with ADO, we observe significantimprovements in heart failure scores, heart size, diastolic function,and BNP level of our subjects especially in the first month afterthe procedure.